HIPK3 modulates autophagy and HTT protein levels in neuronal and mouse models of Huntington disease. Issue 1 (2nd January 2018) - Fu, Yuhua; Sun, Xiaoli; Lu, Boxun
ABSTRACT: Macroautophagy/autophagy is an important cellular protein quality control process that clears intracellular aggregate-prone proteins. These proteins may cause neurodegenerative disorders such as Huntington disease (HD), which is mainly caused by the cytotoxicity of the mutant HTT/Hdh protein (mHTT). Thus, autophagy modulators may regulate mHTT levels and provide potential drug targets for HD and similar diseases. Meanwhile, autophagy function is also impaired in HD and other neurodegenerative disorders via unknown mechanisms. In a recent study, we identified a positive feedback mechanism that may contribute to mHTT accumulation and autophagy impairment in HD. Through genome-scale screening, we identified a kinase gene, HIPK3, as a negative modulator of autophagy and a positive regulator of mHTT levels in HD cells. Knocking down or knocking out HIPK3 reduces mHTT levels via enhancing autophagy in HD cells and in vivo in an HD knock-in mouse model. Interestingly, mHTT positively regulates HIPK3 mRNA levels in both HD cells and HD mouse brains, and this forms a positive feedback loop between mHTT and HIPK3. This loop potentially contributes to autophagy inhibition, mHTT accumulation, and disease progression in HD. The modulation of mHTT by HIPK3 is dependent on its kinase activity and its known substrate DAXX, providing potential HD drug targets. Collectively, our data reveal a novel kinase modulator of autophagy in HD cells, providing therapeutic entry points for HD and similar diseases.